Ethnoveterinary practices of medicinal plants in Selected Districts of West Gojjam Zone, North Western Ethiopia - Ayele, Abebe; Seid, Ali; Bitew Mekonnen, Amare; Adnew, Wubetie; Yemata, Getahun (Ethnobotany Research and Applications, 2025)
Background: In most parts of Ethiopia, the use of medicinal plants to treat different livestock diseases are common. However, the depletion of plant resources and the accompanied erosion and subsequent loss of traditional knowledge posed a threat to this practice. This demonstrates the fact that documentation of ethnoveterinary knowledge is mandatory to reverse the current trend. Hence, the current investigation was aimed at the documentation of ethnoveterinary practices of medicinal plants in selected districts of West Gojjam zone. Methods: Ethnoveterinary data were collected from 30 kebeles (the smallest administrative structure in Ethiopia) at West Gojjam Zone in Amhara region, Ethiopia. The ethnoveterinary data were collected from 30 key and 399 general informants aged > 20 years. Ethnoveterinary data were collected through semi- structured interviews, focus group discussion, and accompanied field walks with individual informants. Descriptive statistics were employed to summarize the data. Ranking methods such as Preference Ranking and Direct Matrix Ranking were used. To draw a graph we used SPSS software version 27. Results: A total of 53 ethnoveterinary medicinal plants were identified belonging to 33 families and 51 genera. Asteraceae and Solanaceae were the most represented families, with five plants species each, followed by Lamiaceae and Euphorbiaceae with four plants each. The most frequently used plant parts to treat livestock diseases were leaves. Crushing was the most common method of remedy preparation followed by pounding. Most of the remedies were administered through orally. The respiratory, spiritual, and injury-related conditions had high Informant Consensus Factor (ICF) value, while Cucumis pustulatus and Withania somnifera showed the highest Fidelity Level (FL) for blackleg and spiritual illnesses, respectively. Preference ranking identified Clerodendrum myricoides as the most preferred for treating anthrax. Direct matrix ranking highlighted Olea europaea and Eucalyptus globulus for their multiple uses in the study area. Similarly, firewood collection had 31 the most plant use diversity in the study area. Conclusion: This study highlights the vital role of ethnoveterinary practices of medicinal plants in treating livestock diseases in Ethiopia’s West Gojjam Zone, emphasizing the wealth of traditional knowledge held by local healers. Despite this valuable knowledge, the research reveals threats from agricultural expansion and urbanization, which jeopardize its preservation. To safeguard these resources, it is crucial to document the knowledge, integrate it into policies, and involve communities in conservation efforts, ensuring their continued availability for future generations and supporting both veterinary care and biodiversity. Keywords: Ethnoveterinary, medicinal plants, indigenous knowledge, West Gojjam Zone, Amhara region